(untitled) (Docentes 2.0 Journal, 2024)
Adolescence is a stage of life with a high incidence of physical, psychological, physiological, and emotional changes; it involves the transition between childhood and adulthood. The present study sought to identify the weaknesses adolescents perceive in themselves, analyze their recurrence, and evaluate their impact on vulnerability to violence. The research is oriented within the sociocultural model, from the pragmatic paradigm, analytical-synthetic method, mixed approach, and concurrent triangulation design. The non-probabilistic sample includes 42 groups of adolescents between 12 and 15 years old from three educational units in El Alto, Bolivia. The methodology is based on cooperative learning and uses the didactic tool "Silhouettes." 52 weaknesses were identified: 6 in the three educational units, 10 in two, and 46 in one. The analysis revealed how these weaknesses can increase the vulnerability of adolescents to being victims of violence, highlighting the need for personal and social strengthening programs. The findings highlight the importance of addressing the perception of weaknesses in adolescents and promoting positive and resilient self-esteem as a preventive tool against violence. Educational and training interventions are required to guide adolescents in this regard.